Sustainable Supply Chain Practices in Local Fashion Brands - Kartika, Nabila (Omnia Tempus, 2024)
This study investigates the sustainable supply chain practices of local fashion brands, focusing on operational dynamics, strategic integration, and their alignment with broader sustainable development goals. Amid rising global concern over the environmental and social impacts of the fashion industry, local brands in emerging economies such as Indonesia play an increasingly critical role. However, the disparity in awareness, resources, and institutional support among these enterprises necessitates a deeper understanding of how sustainability is interpreted and implemented in their supply chains. Employing a qualitative, literature-based research design, this study synthesizes findings from 45 peer-reviewed sources published between 2010 and 2024. Thematic content analysis examined key dimensions, including material sourcing, ethical labor practices, waste reduction, stakeholder engagement, and traceability. The findings reveal that while many local brands engage in eco-conscious practices and artisan-based production, implementation remains fragmented and context-dependent. Strategic integration of sustainability is often constrained by financial limitations, informal labor systems, and the absence of enabling policy frameworks. Nevertheless, local brands demonstrate agility, cultural rootedness, and innovation potential, positioning them as key drivers of change. The study contributes to theoretical discourses in sustainable supply chain management and offers practical implications for entrepreneurs, policymakers, and sustainability advocates. It concludes by emphasizing the importance of systemic support, stakeholder collaboration, and long-term strategic commitment to achieve scalable and inclusive sustainability in the local fashion sector.